Peran Pemimpin Dalam Kohesivitas Kelompok Marching Band Universitas Di Yogyakarta - Saputri, Windy Ayu (2016)
The purpose of this study was to determine the role of leader in the marching band group cohesiveness University in Yogyakarta. Informants in this study were 18 people consisting of 6 Chairman marching bands and 12 marching band members at the university in Yogyakarta. Sampling of this study using purposive sampling. The use of the data in this study using semi-structured interviews. based on the results of interviews conducted on a group leader marching band and members of the marching band can be concluded that the role of the leader in group cohesiveness is the thing to run a leader in charge of a team or group as indispensable even very important in group cohesiveness even have to keep the performance of the group or the marching band achieve group goals that have been set previously.